LITERATURE REVIEW : STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN SIKAP HANDARBENI GURU DI LEMBAGA PAUD - Iriana, Ulfa; Syunu Trihantoyo; Mochamad Nursalim; Amrozi Khamidi; Muhamad Sholeh; Kaniati Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the transformational leadership strategies of school principals in fostering teachers' handarbeni (sense of ownership) in two early childhood education institutions: TK Ananda and TK Al Muttaqin in Driyorejo. Using a qualitative approach and case study design, data was collected through in-depth interviews, participatory observations, and document analysis. The findings indicate that principals who apply transformational leadership principles—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—successfully enhance teachers' emotional engagement and sense of responsibility. Despite challenges such as resource limitations and teacher resistance, these strategies effectively build collaborative and productive work cultures. These results contribute to the development of leadership practices in education to improve school quality.